Kritikan liberalisme terhadap institusi Islam dalam wacana negara sekular: satu penelitian awal - Wahab, Muhammad Rashidi; Wan Ramli, Wan Adli; Mohd Amin, Wan Mohd Azam; Azmi, Mohd Faizul; Khairuddin, Wan Haslan; Mahyuddin, Muhammad Khairi; Yasin, Redwan; Mohd Isa, Nur Ayuni (Jabatan Agama Islam Selangor, 2019)
Liberal ideology seems to be spreading in the Muslim world. One of the criteria of liberalism is challenging and rejecting the established institution that is seen to control the religious understanding and how to interpret it. In Malaysia, one of the established institutions that become the object of criticism and attack of the liberalists is the religious authority. This is very serious matter that requires immediate solution and proper explanation so that the religious institution in Malaysia is well-maintained. This article employs the qualitative methodology in which content and textual analysis technic is applied on the written and electronic materials that include the liberalists’ arguments and comments against the religious institutions of Malaysia. Findings reveal that there are continuous efforts made by liberalist groups to eliminate religious institutions of Malaysia as they subscribe to the concept of secular state which marginalizes the role of religion.